Out-Dated Management Styles In Costa Rican Schools - Cortés Rodríguez, Bayron (2016)
This article discusses the need for changes to occur in the traditional management model of the Costa Rican school system and juxtaposes it against new management strategies. Traditional styles of school administration are analyzed with the objective of adapting them in order to fit the demands of the XXIst century. The article is divided into four sections:: a) Contextualization; b) Outdated management model Educational Centers; c) The Costa Rican education system; d) Proposal management.